Children's spirituality and inclusion: strengthening a child's spirit with community, resilience and joy - Harris, Kathleen I. (International journal of children's spirituality, 2015)
The vision of inclusion speaks to the minds, hearts and spirits of children with disabilities. A meaningful inclusive atmosphere exists when children with and without disabilities are physically engaged and interact with one another as a community in a variety of activities. Spirituality for children with disabilities within an inclusive early childhood classroom requires an education that is intellectual, emotional, social, moral and spiritual. In this type of environment, children with disabilities and peers can flourish in a warm and welcoming community. This paper contributes to the literature and asserts the importance of the forgotten' dimension of early childhood special education. Learning strategies to inform teachers and parents for establishing an inclusive welcoming classroom for children with disabilities are offered by exploring a spiritual curriculum emphasising holistic education with peers through strengths-based projects, small group work and peer-mediated interventions for supporting the interests of each child and developing the capacity to develop resilience and joy.